Increasing the Level of Awareness on Sexually Transmitted Infections (STIs) of Grade 12 Students through #I am un(safe) Campaign - Niala, Samboy D. (Animo Repository, 2024)
Sexually Transmitted Infection (STI) stands out as a crucial health concern, particularly for young adults. Achieving healthy lives and promoting well-being across all age groups aligns with the Sustainable Development Goals, which also emphasize a commitment to ending the AIDS epidemic. The researcher conducted this study at Tagkawayan National High School to elevate Grade 12 students' awareness of Sexually Transmitted Infections (STIs) through the #Iam(un)safe Campaign. Utilizing a quasi-experimental design, the researcher employed pre-tests and post-tests to gauge students' awareness levels. Seventy-five students were purposively selected as respondents, and the pre-test revealed a low awareness level, especially regarding the causes of STIs. To address this, the #Iamunsafe campaign was implemented, including virtual conferences with invited health professionals. Post-tests showed a significant increase in awareness levels, indicating the campaign's effectiveness. Consequently, Tagkawayan National High School should integrate an action plan for all enrolled students and incorporate the campaign into the school's Continuous Improvement Plan. Additionally, endorsing the program to Local Government Units would facilitate assistance from the Rural Health Unit of Tagkawayan in enhancing community awareness, even amid the COVID-19 pandemic.